2009
DOI: 10.1111/j.1464-410x.2009.08671.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience of robotic nephroureterectomy: a hybrid‐port technique

Abstract: OBJECTIVE To report a new technique of robot‐assisted laparoscopic nephroureterectomy (RANU) using a hybrid port, as RANU has recently become a minimally invasive treatment option for upper tract transitional cell carcinoma (TCC). PATIENTS AND METHODS Eleven consecutive patients underwent RANU by one surgeon. The first six patients were repositioned after the nephrectomy, from flank to lithotomy position, and the robot was re‐docked for excision of the distal ureter and bladder cuff. The last five patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…Compared with the case series of Park et al 14 and Eandi et al 15 , which involved redocking the robot system or repositioning of the patient or patient cart during the operation, our method does not require intraoperative redocking or repositioning and, therefore, has a shorter operation time. Hemal et al 16 and Pugh et al 17 reported a case series involving a robotic approach for nephroureterectomy and bladder cuff excision without redocking or repositioning.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with the case series of Park et al 14 and Eandi et al 15 , which involved redocking the robot system or repositioning of the patient or patient cart during the operation, our method does not require intraoperative redocking or repositioning and, therefore, has a shorter operation time. Hemal et al 16 and Pugh et al 17 reported a case series involving a robotic approach for nephroureterectomy and bladder cuff excision without redocking or repositioning.…”
Section: Discussionmentioning
confidence: 90%
“…also reported the technical feasibility of the RANU using the da Vinci robot system for the entire procedure. Their technique could replicate the open surgical technique, and suggested that it is safe and adheres to oncological principles [12]. They introduced the hybrid-port technique and completed the RANU without repositioning the patient and any movement of the patient cart.…”
Section: Discussionmentioning
confidence: 99%
“…The assistant port, which allowed a 12-mm port to be inserted with an 8-mm robotic port, was converted to the port for the second arm as reported by Park et al . [12]. The ureteric orifice defect was closed in two layers with 3 to 0 Monocryl (Ethicon, Guaynabo, Puerto Rico) sutures.…”
Section: Methodsmentioning
confidence: 99%
“…In our view, due to the disadvantages mentioned in the introduction, the method involving a stapler should be abandoned. The other options of distal ureterectomy as a part of CLNUE are as follows: (1) a thermosealing technique [7, 8, 9], (2) the sharp excision of the bladder cuff with intracorporeal suturing (a purely laparoscopic technique) [11, 12, 15] including modification with a bulldog clamp [13], (3) robotic [24], or (4) purse string technique [14]. …”
Section: Discussionmentioning
confidence: 99%